Urgent issues and prospects on investigative interviews with children and adolescents - Talwar, Victoria (Legal and criminological psychology, 2025)
While there has been considerable research on investigative interviews with children over the last three decades, there remains much to learn. The aim of this paper was to identify some of the issues and prospects for future scientific study that most urgently need to be addressed. Across 10 commentaries, leading scholars and practitioners highlight areas where additional research is needed on investigative interview practices with youths. Overarching themes include the need for better understanding of rapport-building and its impact, as well as greater focus on social-cultural and developmental factors and the needs of adolescents. There are calls to examine how interviews are occurring in real-world contexts to better inform best practice recommendations in the field, to find means for ensuring better adherence to best practices among various groups of practitioners, and to understand their importance and impact when not followed, including by those testifying in courts. All reflect the need to better address that recurring challenge of reliably and consistently eliciting accurate and credible information from potentially reluctant young witnesses.